2016
DOI: 10.1016/j.euroneuro.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Receptor interaction profiles of novel psychoactive tryptamines compared with classic hallucinogens

Abstract: The present study investigated interactions between the novel psychoactive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
282
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 271 publications
(302 citation statements)
references
References 73 publications
17
282
2
1
Order By: Relevance
“…Specifically, MDMA mainly induces the transporter-mediated release of serotonin (Hysek et al 2012) and stimulates oxytocin secretion Ramos et al 2013), which has been implicated in the prosocial effects of MDMA (Ramos et al 2013). Additionally, the serotonin receptor agonist LSD (Rickli et al 2016) stimulated oxytocin secretion (Schmid et al 2015a), produced prosocial effects, and enhanced emotional empathy in the MET (Dolder et al 2016). In contrast to MDMA and LSD and our prediction, the present study found that alcohol did not change oxytocin levels in 30 female and 30 male participants at a low dose (0.27 g/kg) as similarly shown for a high dose of alcohol (0.8 g/kg) in seven male subjects (Bershad et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, MDMA mainly induces the transporter-mediated release of serotonin (Hysek et al 2012) and stimulates oxytocin secretion Ramos et al 2013), which has been implicated in the prosocial effects of MDMA (Ramos et al 2013). Additionally, the serotonin receptor agonist LSD (Rickli et al 2016) stimulated oxytocin secretion (Schmid et al 2015a), produced prosocial effects, and enhanced emotional empathy in the MET (Dolder et al 2016). In contrast to MDMA and LSD and our prediction, the present study found that alcohol did not change oxytocin levels in 30 female and 30 male participants at a low dose (0.27 g/kg) as similarly shown for a high dose of alcohol (0.8 g/kg) in seven male subjects (Bershad et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is much interest in its therapeutic potential (Baumeister et al 2014; Davenport 2016; Gasser et al 2014; Gasser et al 2015; Krebs and Johansen 2012; Kupferschmidt 2014). Only one modern study has tested the therapeutic effects of LSD in patients (Gasser et al 2014), whereas several clinical trials have recently evaluated the therapeutic potential of psilocybin (Bogenschutz et al 2015; Carhart-Harris et al 2016a; Garcia-Romeu et al 2015; Griffiths 2016; Grob et al 2011; Guss 2016), a similar serotonergic hallucinogen (Rickli et al 2016). A series of studies showed that psilocybin acutely induced mystical experiences in healthy subjects and patients (Garcia-Romeu et al 2015; Griffiths et al 2008; Griffiths et al 2011; Griffiths et al 2006; MacLean et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Psychostimulant and hallucinogenic amphetamines, numerous ergoline derivatives including ergometrine, dihydroergotamine, and LSD, as well as the antiparkinsonian agents bromocriptine and lisuride, display agonistic activity at the rat [59] and mouse [51] TAAR 1 receptor expressed on HEK-293 cells. Simmler et al showed that LSD has relatively high affinity for TAAR 1 in rat but lower in mice and humans [137], for the first time, our laboratory showed that the injection of EPPTB (5 mg/kg, i.v.…”
Section: In the Deep Of The Mechanism: Who Are The Players?mentioning
confidence: 99%
“…The inference was that modulators of serotonin receptors might be useful in the treatment of schizophrenia [45,46]. Multiple lines of evidence indicate that LSD acts through the serotonergic system, binding the 5-HT 2A receptor as a partial agonist, even at human cloned 5-HT 2A receptor [47,48,49,50,51], and the 5-HT 1A receptor as an agonist/partial agonist [52,53]. However, studies have also pointed out the involvement of the dopaminergic [50,54] and glutamatergic [55] systems in LSD’s mechanism of action.…”
Section: Introductionmentioning
confidence: 99%